Cement board filled with aged oil palm trunk strands: Effect of board densities and strand sizes / Nurnabilah Hanee Che Ab Rahim and Nor Yuziah Mohd Yunus - Che Ab Rahim, Nurnabilah Hanee; Mohd Yunus, Nor Yuziah (Universiti Teknologi MARA Cawangan Pahang, 2021)
Wood cement board (WCB) combines organic and inorganic material; wood and cement. The inclusion of wood fiber into cement allows reduction of weight for finished product and adds an amount of carbon capture character in the WCB. In this study, the WCB combined aged oil palm strands (organic) obtained from the trunk and Portland cement (inorganic). The experiments aimed to determine the physical (thickness swelling and water absorption) and mechanical (bending strength and screw withdrawal) properties of WBC at 3 densities; 1300 kg/m3, 1100 kg/m3 and 900 kg/m3. Two particle sizes of 30 mm and 50mm of the oil palm trunk strands were utilized. The result showed that generally, WBC with density of 1300kg/m3 has higher mechanical properties and better dimensional stability. The highest bending strength was presented by WCB with 1300kg/m3 density with 50mm strands size, displaying modulus of elasticity 1315.6 MPa and modulus of rupture 4.6 MPa. Therefore, it is possible to use aged oil palm strand in WCB.